Measuring the Games Influence on Improving English Proficiency - Reni Dwi Pertiwi; Erdhi Widyarto N. (SISFORMA, 2014)
English is now used as an international language, so that every person in order to communicate at the international level are required this language. To improving english proficiency, people used native speaker, course, story book, film game and etc. Games or better known as PC gaming is another alternative in improving the English proficiency. Beside this is fun, player required to read and listen the story game to finish the game. So that player can improve English proficiency while the player play game. In this paper, author present what game are fun and not boring also can improving English proficiency. The measuring improving English proficiency is observed from reading,writing, listening and grammarKeyword: English, Game, improving ,Proficiency